Pengaruh Teknik Pemberian Asi Melalui Direct Breastfeeding dan Cup Feeding Terhadap Saturasi Oksigen pada Bayi Prematur di Ruang Perinatal - Aulia Zulfa Umi Arifah; Nopi Nur Khasanah; Herry Susanto (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2025)
Preterm infants have suction and swallowing reflexes that are not well coordinated so that they are prone to aspiration which is characterized by a decrease in oxygen saturation during breastfeeding. Breastfeeding can be given using OGT until the baby has the full ability to switch to Direct Breastfeeding and Cup Feeding. This study used quantitative approach method with quasi experimental research design with two-group pre-test post-test control group design. Data collection was done by direct observation. The research sample amounted to 22 respondents with 11 babies in each group using consecutive sampling. Data were tested using Paired t-test and the test of differences between groups using Unpaired t-test. The results showed a significant effect between direct breastfeeding and cup feeding in premature infants (p value = 0.018; p value = 0.034). And there is no significant difference between breastfeeding through the two methods on oxygen saturation in premature babies (p value = 0.590). In conclusion, this study found that direct breastfeeding is more recommended because it has a higher impact on the oxygen saturation value of preterm infants than cup feeding. Although both have a positive effect on infant oral motor skills in preterm infants